Iron-catalysed 1, 2-acyl migration of tertiary α-azido ketones and 2-azido-1, 3-dicarbonyl compounds. Issue 22 (16th October 2019) - Yang, Tonghao; Lin, Yajun; Yang, Chaoqun; Yu, Wei
Abstract : Synthesis of enamides via 1, 2-acyl migration of tertiary α-azido ketones was accomplished efficiently by the catalysis of FeBr2 and Et3 N. Abstract : Iron-catalysed 1, 2-acyl migration of tertiary α-azido ketones and 2-azido-1, 3-dicarbonyl compounds provides a simple and atom-economical approach toward enamides and isoquinolones. This paper reports two catalyst systems for these transformations which employ iron(ii ) complexes [Fe(dpbz)]Br2 (dpbz = 1, 2-bis(diphenylphosphino)benzene) and FeBr2 /Et3 N, respectively. [Fe(dpbz)]Br2 was found to be highly effective at converting 2-azido-2, 3-dihydro-1 H -inden-1-ones to isoquinolones. The reagent combination of FeBr2 /Et3 N, on the other hand, exhibited a broader catalytic scope, owing to the beneficial effect of Et3 N. This latter catalyst system enables 2-azido-2-methyl-1, 3-dicarbonyl compounds to be converted to the corresponding enamides under mild conditions in good yields.